Perception of Insurance According to Generation Z Teacher Candidates (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
Insurance at this time is very necessary for the community because of the many problems that occur both in the form of property and health-related losses. Significant problems with unbalanced growth rates resulting in inequality and affecting carrying capacity. The impact of this problem makes humans respond by means of insurance. But does generation z, especially prospective teachers, have insurance or is the unawareness of generation z in insurance. So, qualitative research methods with descriptive research types.